A foreign policy for the Left - Walzer, Michael (Yale University Press, 2018)
Something that has been needed for decades: a leftist foreign policy with a clear moral basis Foreign policy, for leftists, used to be relatively simple. They were for the breakdown of capitalism and its replacement with a centrally planned economy. They were for the workers against the moneyed interests and for colonized peoples against imperial (Western) powers. But these easy substitutes for thought are becoming increasingly difficult. Neo-liberal capitalism is triumphant, and the workers' movement is in radical decline. National liberation movements have produced new oppressions. A reflexive anti-imperialist politics can turn leftists into apologists for morally abhorrent groups. In Michael Walzer's view, the left can no longer (in fact, could never) take automatic positions but must proceed from clearly articulated moral principles. In this book, adapted from essays published in Dissent, Walzer asks how leftists should think about the international scene--about humanitarian intervention and world government, about global inequality and religious extremism--in light of a coherent set of underlying political values.